An Overview of Open Relationship Behaviors among Homosexual (Gay) Individuals Using Online Dating Applications - Henry Franco Eduard Tobe; Ratriana Yuliastuti Endang Kusumiati (Yayasan Ilomata, 2026)
This study aims to explore the behavioral dynamics of open relationships among homosexual (gay) individuals who use online dating applications, focusing on subjective experiences derived from a small-scale qualitative inquiry. The study is motivated by the increasing use of digital platforms within the gay community, which may facilitate more flexible and non-monogamous relational arrangements. A qualitative method with a phenomenological approach was employed to examine lived experiences in depth. Data were collected through in-depth interviews with two participants who are engaged in open relationships and actively use dating applications. The findings, based on inductive thematic analysis of participants’ narratives, indicate that open relationships are not merely understood as expressions of sexual freedom, but as ongoing processes of negotiating emotional needs, intimacy, and personal autonomy. Seven recurrent themes consent, self-awareness, communication, honesty, boundaries, trust, and negotiated forms of fidelity and commitment emerged as key features within participants’ accounts. These themes were developed inductively while being interpreted in relation to existing theoretical perspectives on consensual non-monogamy. Within this limited empirical context, open relationships reflect an alternative construction of fidelity grounded in transparency and emotional responsibility, particularly in tension with dominant cultural norms that privilege monogamy. Given the study’s reliance on two participants, the findings are not intended for generalization but instead provide context-bound insights into individual meaning-making processes. The study contributes to social psychological discourse by offering a phenomenologically grounded account of emotional ethics in non-monogamous relationships and highlights implications for culturally sensitive counseling practices for LGBTQ+ clients in Indonesia.